Influencia de la página de Facebook de la Universidad Politécnica Salesiana, sede Guayaquil, como medio de información para los estudiantes - Rodas, Betty Isabel (2016)
Given the need for professorial training process in Education Science and its social significance, the objective of this work is to reflect on the training in university teaching from its application in practice. From the theoretical foundations of the educability and educatividad, an interactive program that would combine presentiality using virtual resources, was conceived through a course that would privilege the professional exchange with the possibilities of using the Virtual Classroom Cooperative Learning (AVAC) of the University. It was intended to enable socialization and assimilation cooperatively content, paying special attention to the theory linking practice. In the evaluative plane it was helped to reaffirm the sense of belonging to the teachingprofession, regardless of the subjects head into the teaching-learning process. 94% of participants said the positive impact of the ongoing transformation of teaching. In this area the significance of the teaching work to finalize highlighted the links between science and subject to contribute to the integral formation of students, in the framework of the substantive processes of higher education.